A real-world study of palbociclib plus endocrine therapy with or without a short course chemotherapy in the first-line treatment of HR-positive HER2-negative metastatic breast cancer - Li, Xiangjun; Song, Yuhua; Lv, Meng; Wang, Yongmei; Gao, Xueqiang; Ma, Tianyi; Ma, Teng; Liu, Changgen; Sun, Xinyi; Wang, Haibo; Mao, Yan (Frontiers in Oncology, 2025)
BackgroundTo investigate the efficacy of palbociclib plus endocrine therapy (ET) as the initial treatment compared with post-chemotherapy maintenance therapy in the first-line treatment of hormone receptor-positive (HR-positive), human epidermal growth factor receptor 2-negative (HER2-negative) metastatic breast cancer (MBC).MethodsA total of 110 patients with HR-positive HER2-negative MBC were enrolled in this study between 2018 and 2023. Progression-free-survivals (PFS) and Overall Survival (OS) of palbociclib plus ET as the initial treatment (group A, n:78) or as post-chemotherapy maintenance therapy (group B, n:32) were calculated. We used the multivariable Cox model to investigate the relationship between each factor and prognosis and performed subgroup analysis.ResultsThe median duration of follow-up across the cohort was 45.3 months (95% CI, 42.7 to 50.9 months) in all patients. Statistical analysis revealed no significant difference in PFS between the two groups (p=0.21). 50% was the objective response rate (ORR) for both groups. The disease control rate (DCR) for group A was 95.1% (95%CI 0.88 to 0.98), and for group B, it was 100% (95% CI 0.89 to 1.00). Multivariate Cox regression analysis indicated that the initial administration of palbociclib plus ET was significantly correlated with improved OS (Hazard Ratio [HR] = 0.36, 95% CI, 1.20 to 11.14, p < 0.05).ConclusionThis real-world study revealed that the commencement of therapy with palbociclib in synergy with ET was preferable to effective chemotherapy followed by palbociclib plus ET.